THE TRANSLATION OF IDIOMS AND THE PROBLEMS OF CROSS-LINGUISTIC MISUNDERSTANDING - Asqarova Madina Boymurod qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the challenges inherent in translating idioms across languages and the potential for cross-linguistic misunderstanding. It examines the nature of idioms, their cultural embeddedness, and the strategies employed by translators to convey idiomatic meanings. Through various examples and an analysis of existing literature, this study highlights the complexities involved in idiomatic translation and proposes approaches to mitigate misunderstandings in cross-cultural communication.